Customer Retention in E-Payments: Identifying the Key Determinants - Bhattarai, Taranath (International Research Journal of Parroha, 2025)
Effective utilization of community resources provides significant opportunities for practice-oriented learning. Such integration fosters skill-based education, which in turn contributes to the development of competent human resources capable of adapting to both national and international contexts while reducing unemployment. This study explores the relationship between community resources and skill-oriented education, with a particular focus on embedding local potentialities into the school curriculum. Employing a qualitative research design, data were collected through Participatory Rural Appraisal (PRA), classroom observations, and semi-structured interviews. Thematic analysis was applied within an interpretive paradigm to analyze the data. Findings indicate that communities possess abundant resources and local expertise that, if systematically incorporated, can enhance students’ skill development. The study further highlights strategies for designing contextually relevant curricula that align with local needs and resources, thereby promoting practical and sustainable education in the study area and beyond.